Robotic vehicle with side scanning sonar for underwater surveillance of shallow water reservoirs - Iastrebov, Viatcheslav (2020)
Design and experimental investigations of a side scanning sonar system developed for scanning the underwater environments for shallow water applications is described in this paper. A self-propelled floating vehicle with two arrays of side looking sonar sensors and a data controller is designed as the scanning platform. Data from the sonar are sent through wireless mode to a computer and analyzed using special purpose software. Objects floating below the water level or lying on the bottom surface of still water reservoirs can be easily identified using this system. The water condition or other environmental factors have little effect on the quality of the scanned images. Design details of the vehicle and experimental results are presented.